2001
DOI: 10.1089/109493101750527006
|View full text |Cite
|
Sign up to set email alerts
|

The VEPSY Updated Project: Virtual Reality in Clinical Psychology

Abstract: Many of us grew up with the naive assumption that couches are the best used therapeutic tools in psychotherapy. But tools for psychotherapy are evolving in a much more complex environment than a designer's chaise lounge. In particular, virtual reality (VR) devices have the potential for appearing soon in many consulting rooms. The use of VR in medicine is not a novelty. Applications of virtual environments for health care have been developed in the following areas: surgical procedures (remote surgery or telepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Moreover, the therapy is being carried out in the therapist's office, which preserves confidentiality. 16 Several controlled studies already confirmed the efficiency of virtual exposure for phobic disorders such as acrophobia, 17 flying phobia, 18 arachnophobia, 19 or agoraphobia. 20 Two studies have investigated the efficacy of virtual reality therapy in the treatment of the specific anxiety subtype of social phobia, more precisely the fear of public speaking.…”
mentioning
confidence: 95%
“…Moreover, the therapy is being carried out in the therapist's office, which preserves confidentiality. 16 Several controlled studies already confirmed the efficiency of virtual exposure for phobic disorders such as acrophobia, 17 flying phobia, 18 arachnophobia, 19 or agoraphobia. 20 Two studies have investigated the efficacy of virtual reality therapy in the treatment of the specific anxiety subtype of social phobia, more precisely the fear of public speaking.…”
mentioning
confidence: 95%
“…">IntroductionVirtual Reality (VR) has been usually described as a collection of technological devices: a computer capable of interactive 3D visualization, a head-mounted display and data gloves equipped with one or more position trackers [1]. The trackers sense the position and orientation of the user and report that information to the computer which updates the images for display in real time.…”
mentioning
confidence: 99%
“…This might happen because there is substantial difficulty inducing an anxious mental scenario in some PTSD patients. 8 The increasing accessibility to powerful personal computers and 3D visualization techniques has made possible the development of virtual reality (VR) and its use on mental health. This technological technique (tech-tech) is being used to treat patients with several anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%